2016
DOI: 10.1016/j.jvolgeores.2016.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Computer aided detection of transient inflation events at Alaskan volcanoes using GPS measurements from 2005–2015

Abstract: Analysis of transient deformation events in time series data observed via networks of continuous Global Positioning System (GPS) ground stations provide insight into the magmatic and tectonic processes that drive volcanic activity. Typical analyses of spatial positions originating from each station require careful tuning of algorithmic parameters and selection of time and spatial regions of interest to observe possible transient events. This iterative, manual process is tedious when attempting to make new disc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…In March 1996, an intense earthquake swarm was accompanied by uplift as much as 60 cm on the west flank of Akutan [Lu et al, 2000b[Lu et al, , 2005. Small inflation events occurred in 2008 [Ji and Herring, 2011;Li et al, 2016] and in 2011 [Walwer et al, 2016], identified with Global Positioning System (GPS) data. The 1996The , 2008, and 2011 events did not culminate in an eruption, and they may be episodes of magma accumulation in a shallow reservoir underneath Akutan.…”
Section: Introductionmentioning
confidence: 99%
“…In March 1996, an intense earthquake swarm was accompanied by uplift as much as 60 cm on the west flank of Akutan [Lu et al, 2000b[Lu et al, , 2005. Small inflation events occurred in 2008 [Ji and Herring, 2011;Li et al, 2016] and in 2011 [Walwer et al, 2016], identified with Global Positioning System (GPS) data. The 1996The , 2008, and 2011 events did not culminate in an eruption, and they may be episodes of magma accumulation in a shallow reservoir underneath Akutan.…”
Section: Introductionmentioning
confidence: 99%